Grid-line watermarking: A novel method for creating a high-performance text-image watermark - Yawai, Wiyada; Hiransakolwong, Nualsawat (My University, 2013)
This study aims to discover an effective method to watermark any text image in any language. The ultimate goal of this work is to generate invisible and more robust watermarks, increase the hiding capacity, and identify any change in the original text. Generally these are the limitations of most text-image watermarking methods. Using a grid of horizontal and vertical lines is one of the most effective methods to overcome these limitations. These grid lines run across textimage character-skeleton lines to finely mark and detect watermarks on these line-character intersection points; there is one intersection for one specific zero watermark pixel. Each intersection point is defined by one hiding bit of the watermark such that the more reference horizontal and vertical lines of grid pattern are plotted, the more points of intersection are obtained. This approach increases the hiding-bit capacity to watermark embedding, which is a disadvantage shared by many text-image watermarking methods. In addition, if all positions of all intersection points are collected, these points will act as the identity reference points of all original characters to verify their integrities after they are modified.
Keywords: Collinear points; Cross ratio; Digital watermarking; Grid lines; Integrity; Text image; Zero watermark